2022
DOI: 10.1002/csc2.20776
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of resistance to Fusarium verticillioides ear rot in maize inbred lines of southern, West and Central Africa origin

Abstract: Maize (Zea mays L.) is an important crop in sub-Sahara Africa for both human consumption and livestock feed. Maize use is often limited by ear-rotting fungi, some of which produce deleterious secondary metabolites. The aim of this study was to determine the inheritance of resistance to Fusarium verticillioides as an indirect way of selecting for resistance to secondary metabolites such as the mycotoxin fumonisin that is produced by this fungus, under artificial inoculation and natural infection. Twelve inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…In Canada, inbred lines with high resistance to FER and GER have been reported by Reid et al (2001a;2001b;2003). Similarly, potential sources of resistance to FER were identified in China (Guo et al, 2020) and tropical regions including southern, western and central Africa (Tembo et al, 2022). The exploitation of existing resistance sources in breeding programs requires a clear understanding of the genetic architecture of FER-and GER-related traits, and underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, inbred lines with high resistance to FER and GER have been reported by Reid et al (2001a;2001b;2003). Similarly, potential sources of resistance to FER were identified in China (Guo et al, 2020) and tropical regions including southern, western and central Africa (Tembo et al, 2022). The exploitation of existing resistance sources in breeding programs requires a clear understanding of the genetic architecture of FER-and GER-related traits, and underlying molecular mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, commercially available maize cultivars in Africa have not been tested for specific resistance to Fusarium species (Tembo et al, 2022). Previous studies in South Africa, and Nigeria reported potential resistance of some maize-inbred lines to F. verticillioides and fumonisin accumulation (Olowe et al, 2015;Small et al, 2012).…”
Section: On-field Preventive Methodsmentioning
confidence: 99%
“…That is, scale‐up education on the use of resistant cultivars, appropriate soil amendment methods, proper weed management, and harvesting techniques should be facilitated. Unfortunately, commercially available maize cultivars in Africa have not been tested for specific resistance to Fusarium species (Tembo et al., 2022 ). Previous studies in South Africa, and Nigeria reported potential resistance of some maize‐inbred lines to F .…”
Section: Innovative Strategies To Reduce Risk Levels Of Zearalenone I...mentioning
confidence: 99%
“…Maize ear rot resistance results from both additive and dominance effects (Boling & Grogan, 1965; Löffler et al., 2011; Tembo et al., 2022). Although some studies have reported additive × dominance or dominance × dominance digenic interaction effects (Nankam & Pataky, 1996), both parents should possess resistance alleles to obtain highly resistant hybrids (Hung & Holland, 2012; Netshifhefhe et al., 2018; Ouko et al., 2020).…”
Section: Introductionmentioning
confidence: 99%